Pengaruh Latihan Sirkuit terhadap Peningkatan Daya Tahan (VO2Max) pada Pemain Persigar Garut - Deidad Darussalam; Asep Angga Permadi; Z. Arifin; Azhar Ramadhana Sonjaya (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to examine the effectiveness of circuit training programmes on improving endurance (VO2Max) in Persigar Garut football players. Physical endurance is important for players to be able to last for 90 minutes of play. Materials and methods. The method used was a quasi-experiment with a One Group Pretest-Posttest Design. The research sample consisted of 25 active Persigar Garut players, with measurements taken using the Multistage Fitness Test. The Circuit Training programme was administered for 4 weeks with a frequency of 3 times per week. Results. The results showed a significant increase in average VO2Max, from 47.94 (Pretest) to 55.13 (Posttest), an increase of 15.00%. Paired t-test analysis showed a very significant difference (Sig. 2-tailed < 0.001). Conclusion. The conclusion of this study is that Circuit Training has a significant and positive effect on increasing the endurance capacity (VO2Max) of Persigar Garut football players. This increase is due to the characteristics of Circuit Training, which stimulates the cardiorespiratory system intensely and repeatedly, as well as its effectiveness in maximising the body's ability to absorb and utilise oxygen.